Enhanced Cytotoxicity of Niosomal Copper Schiff-Base Complexes in MCF-7 Cells: Substituent Effects and Delivery Efficiency - Forouzani, Hosniyeh; Zare Mehrjardi, Ehsan; Kargar, Hadi; Forouzani, Houriyeh; Dehghani Ashkezari, Mahmood (Asian Pacific Journal of Cancer Biology, 2026)
Introduction: Breast cancer is currently the leading cause of cancer-related mortality among women worldwide. If urgent actions are not taken, the number of women diagnosed with breast cancer globally is projected to nearly double. Treating cancer cells is a complex process due to the presence of diverse biological pathways. Therefore, the simultaneous delivery of multiple drugs can exert a synergistic effect on the treatment process. Additionally, nanocarriers must exhibit high biocompatibility with healthy cells. Advancements in nanocarrier-mediated drug delivery offer promising strategies for improving anticancer agent efficacy. Objective: This study synthesized two novel copper Schiff-base complexes N, N’-bis (3-ethoxysalicylidene)-2,2-dimethyl-1,3-propanediamine Cu (II) (CuL3OEt) and N, N’-bis (5-bromosalicylidene)-2,2-dimethyl-1,3-propanediamine Cu (II) (CuL5Br) and compared their cytotoxicity against MCF-7 breast cancer cells in free and niosome-encapsulated forms. Materials and Methods: Niosomes were prepared via the thin-film hydration method to enhance delivery efficiency. Characterization using Atomic Force Microscopy (AFM) and Dynamic Light Scattering (DLS) revealed uniform nanoparticles (87.8–243.3 nm). Results: Cytotoxicity, assessed via MTT assay, showed niosome-encapsulated forms significantly reduced IC₅₀ values (e.g., CuL3OEt: 8.24 μg/mL vs. 80.65 μg/mL free form at 72 hr, p < 0.05), indicating improved potency. Substituent effects (ethoxy vs. bromo) influenced outcomes, linked to hydrophobicity differences (logS -4.788 vs. -5.75). Given the higher molecular weight of CuL5Br (530 g/mol) compared CuL3OEt (460 g/mol), the loading efficiency was 13.26% and 90.43%, respectively. Conclusion: These findings highlight niosomal delivery’s potential to enhance Cu Schiff-base complex efficacy, laying a foundation for further preclinical studies.